The Relationship Of Covid-19 Prevention Behavior With Quality of Life in Mutihan, RT 05, Wirokerten Village, Banguntapan Bantul, Yogyakarta Year 2020 - Zulchaidir K Lewenussa (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
In 2020 the spread of Covid-19 from person to person will be the main source of transmission, so the spread will become more aggressive. The enormous ability of this virus to infect and spread is evidenced by the note that so far there are still many people infected with Covid-19 with an increasing number. Cases in Indonesia also continue to increase, until March 29, 2020, there have been 1,115 cases with 102 deaths, while the largest number of cases of the COVID-19 outbreak in Yogyakarta is in Bantul district, Banguntapan sub-district with a total ODP of 150 people, PDP (1 died, 1 recovered, 6 are positive, and 24 are still under surveillance). To determine the relationship between COVID-19 prevention behavior and quality of life in Dusun Mutihan RT 5 Wirokerten, Banguntapan, Bantul, Yogyakarta. This type of research is a quantitative descriptive study with a cross-sectional approach. The sampling technique in this study was random sampling with as many as 65 samples taken. Based on the statistical results using the chi-square test, it was obtained X2 count of 28.502a, a P value of .000 (P-0.10) which indicates that there is a relationship between covid-19 prevention behavior and quality of life in Mutihan village rt 05 Banguntapan Bantul Yogyakarta. There is a relationship between Covid-19 prevention behavior and quality of life in Dusun Mutihan Rt 5 Wirokerten, Banguntapan, Bantul, Yogyakarta.